Understanding the growth mechanism of vertically aligned graphene and control of its wettability. (July 2016) - Zhang, L.X.; Sun, Z.; Qi, J.L.; Shi, J.M.; Hao, T.D.; Feng, J.C.
Abstract: In this paper, vertical graphene nanosheets (VGNs) were grown by PECVD method. Based on SEM, TEM, Raman and XPS spectrum analysis, the defect-guided growth mechanism of the VGNs was proposed. The effects of defects on the formation of VGNs were discussed in detail. In addition, different densities of defects were produced on the grown VGNs by adjusting different Ar ion sputtering durations. Contact angles (CA) were measured to illustrate the effect of the density of the defects on the wettability of the VGNs. The CA decreases from 102.9° (without sputtering) to 91.5°, 75.1° and 47.8° respectively as the density of the defects increases. It confirms that the wettability of the VGNs could be controlled from hydrophobic to hydrophilic nature by introducing defects.